Reverse osmosis concentrated water treatment agent and preparation method thereof
By modifying bentonite powder, titanium-based MOF and hydrogel membranes are generated, solving the clogging and scaling problems of traditional reverse osmosis membrane technology. This achieves efficient removal of heavy metals and organic pollutants, reduces conductivity, and improves the long-lasting effect and environmental friendliness of scale inhibitors.
Patent Information
- Application Number
- CN202511082131.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-04
- Publication Date
- 2025-10-28
AI Technical Summary
Existing reverse osmosis membrane technology is prone to clogging, frequent cleaning, incomplete removal of pollutants, and low water production when treating industrial wastewater. Furthermore, traditional scale inhibitors have insufficient long-term scale inhibition effect, slow biodegradation rate, and potential environmental impact. In addition, the ion exchange capacity of existing bentonite and diatomite mixtures is insufficient, leading to serious scaling and fouling problems.
After alkali washing and acid washing of bentonite powder, it is esterified with phenylboronic acid and 2,5-hydroxyterephthalic acid, and then reacted with titanium tetrachloride to form a titanium-based MOF. Subsequently, it is treated with γ-methacryloyloxypropyltrimethoxysilane to form a hydrogel membrane, and then copolymerized with zinc acrylate and N-isopropylacrylamide to form a treatment agent with high specific surface area and porosity. Boron and zinc elements are introduced to improve adsorption and ion exchange capacity.
It significantly improves the adsorption of manganese and calcium ions, reduces the hardness, turbidity and conductivity of concentrated water, avoids scaling, reduces environmental hazards, improves the utilization rate of sunlight and photocatalytic activity, and achieves long-lasting scale inhibition effect.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wastewater treatment technology, specifically a reverse osmosis concentrate treatment agent and its preparation method. Background Technology
[0002] Currently, most industrial enterprises in China use reverse osmosis (RO) membrane technology for process wastewater reuse. However, existing RO treatment processes generally suffer from drawbacks such as easy clogging, frequent cleaning, incomplete pollutant removal, low permeate flow rate, and high operating pressure. One of the main reasons is the high electrolyte concentration in the raw water. Although conventional pretreatment processes involving the addition of inorganic coagulants can remove some heavy metal ions and organic pollutants, they cannot minimize the electrolyte concentration in the water, i.e., they cannot effectively reduce the conductivity of the water. Studies have shown that scaling becomes increasingly severe as conductivity increases. Therefore, the conductivity of the feed water to the reverse osmosis system will affect the permeate flow rate.
[0003] Traditional reverse osmosis concentrate antiscalants are generally classified into the following categories: phosphorus-containing small molecule antiscalants, high molecular weight polymer antiscalants, and natural dispersants. However, these traditional high molecular weight polymers suffer from the drawbacks of self-entanglement and self-adhesion. To solve the problems of traditional antiscalants, dendritic polymer antiscalants have been developed. Their unique dendritic spherical structure has a good effect on attracting and inhibiting fouling, and it also overcomes the drawbacks of self-entanglement and self-adhesion of traditional polymers, making it more stable. Moreover, it is phosphorus-free, which can avoid the problems of microbial growth and membrane fouling caused by phosphorus components. However, the existing dendritic polymer antiscalants have insufficient long-term antiscaling effect and slow biodegradation rate, which may have potential impacts on the ecological environment.
[0004] Chinese patent announcement CN113929250B discloses a zero-discharge process and treatment system for cold-rolled reverse osmosis concentrate. This system utilizes a mixture of bentonite and diatomaceous earth, with sodium chloride intercalation and diethylenetriaminepropyltrimethoxysilane grafting, to adsorb manganese and calcium ions in the concentrate. However, this method relies solely on sodium chloride intercalation and diethylenetriaminepropyltrimethoxysilane grafting, resulting in a low specific surface area and insufficient ion exchange capacity. This fails to meet the adsorption requirements for manganese and calcium ions during the cold rolling process, leading to severe scaling and fouling in subsequent disc tube reverse osmosis systems, and even equipment failure. Summary of the Invention
[0005] The purpose of this invention is to provide a reverse osmosis concentrate treatment agent and its preparation method. Bentonite powder is alkali-washed and acid-washed, and then the carboxyl groups and borate groups of phenylboronic acid on the surface undergo an esterification reaction with the hydroxyl groups of 2,5-hydroxyterephthalic acid. Then, it is reacted with titanium tetrachloride in situ through a hydrothermal reaction to generate a titanium-based MOF. After treatment with γ-methacryloyloxypropyltrimethoxysilane, it is copolymerized with zinc acrylate and N-isopropylacrylamide to form a hydrogel membrane. The introduction of boron and zinc elements into the treatment agent, the high specific surface area of the hydrogel membrane and activated bentonite, and the porosity of the titanium group can significantly increase the adsorption and ion exchange capacity of the treatment agent, and improve the adsorption of manganese and calcium ions.
[0006] The objective of this invention can be achieved through the following technical solutions:
[0007] A method for preparing a reverse osmosis concentrate treatment agent includes the following steps:
[0008] Step 1: After alkali washing and acid washing of bentonite powder, activated bentonite powder is obtained. The carboxyl groups and borate groups of phenylboronic acid on the surface of the activated bentonite powder undergo an esterification reaction with the hydroxyl groups of 2,5-hydroxyterephthalic acid. Then, titanium-based MOF is generated in situ through hydrothermal reaction with titanium tetrachloride to obtain composite bentonite powder.
[0009] Step 2: Graft the hydroxyl groups on the surface of the composite bentonite powder with the silanol groups generated by the hydrolysis of γ-methacryloyloxypropyltrimethoxysilane to obtain functionally modified bentonite powder.
[0010] Step 3: A reverse osmosis concentrate treatment agent is obtained by copolymerizing the double bonds in functionally modified bentonite powder, zinc acrylate, and N-isopropylacrylamide under the action of an initiator.
[0011] Furthermore, the specific preparation steps for activated bentonite powder are as follows:
[0012] Bentonite powder and a 6M NaOH solution were added to a reaction vessel and stirred for 6-7 hours at 100-110℃ and 50-60 r / min. The mixture was filtered, and the filter cake was washed with deionized water and anhydrous ethanol until the final washing solution was neutral. The mixture was then vacuum dried at 100-110℃ for 10-12 hours to obtain alkaline-etched bentonite. Alkaline-etched bentonite and a 5M HCl solution were added to a reaction vessel and stirred for 6-7 hours at 80-90℃ and 50-60 r / min. The mixture was filtered, and the filter cake was washed with deionized water and anhydrous ethanol until the final washing solution was neutral. The mixture was then vacuum dried at 100-110℃ for 10-12 hours to obtain activated bentonite powder.
[0013] Furthermore, the ratio of bentonite powder to NaOH solution is 200-220g: 120-130mL.
[0014] Furthermore, the ratio of alkaline etching bentonite to HCl solution is 150-160g: 60-70mL.
[0015] Furthermore, the specific preparation steps of the composite bentonite powder are as follows:
[0016] Activated bentonite powder, phenylboronic acid, 2,5-hydroxyterephthalic acid, and deionized water were added to a reaction vessel and stirred for 1 hour at 20-25°C and 500-600 r / min. Then, triethylamine was added and stirring was continued for 1 hour. Next, a mixed solution of sodium hexadecyl sulfate and 60-70 wt% ethanol solution was added, and the mixture was heated to 120-130°C and stirred for 20-30 minutes. Then, titanium tetrachloride was added and stirring was continued for 24-26 hours. The mixture was filtered, and the filter cake was washed 2-3 times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60-80°C for 1-2 hours to obtain composite bentonite powder.
[0017] Furthermore, the ratio of activated bentonite powder, phenylboronic acid, 2,5-hydroxyterephthalic acid, deionized water, triethylamine, sodium hexadecyl sulfate, ethanol solution, and titanium tetrachloride is 130-140g: 50-60g: 100-110g: 2-3L: 6-9mL: 12-13g: 120-140mL: 50-60g.
[0018] Furthermore, the specific preparation steps for functionally modified bentonite powder are as follows:
[0019] Composite bentonite powder, anhydrous ethanol, and deionized water are added to a reaction vessel and stirred for 20-30 minutes at 50-60℃ and 500-600 r / min. Then, γ-methacryloyloxypropyltrimethoxysilane is added, and the pH value is adjusted to 3-4 with hydrochloric acid solution. The reaction is continued to be stirred for 6-7 hours. After filtration, the precipitate is washed 2-3 times with deionized water and anhydrous ethanol and dried under vacuum at 60-80℃ for 1-2 hours to obtain functionally modified bentonite powder.
[0020] Furthermore, the ratio of composite bentonite powder, anhydrous ethanol, deionized water and γ-methacryloyloxypropyltrimethoxysilane is 120-130g: 200-300mL: 300-400mL: 50-60mL.
[0021] Furthermore, the specific preparation steps of the reverse osmosis concentrate treatment agent are as follows:
[0022] Functionally modified bentonite powder, zinc acrylate, deionized water, and N-isopropylacrylamide were added to a reactor and stirred for 20-30 minutes at 20-25℃ and 400-500 r / min. The mixture was then heated to 70-80℃, and ammonium persulfate was added. Under a nitrogen atmosphere, the mixture was stirred and reacted for 6-7 hours. The mixture was then filtered, and the filter cake was washed 2-3 times with petroleum ether and deionized water, respectively. The cake was then vacuum dried at 60-80℃ for 1-2 hours and pulverized to obtain a reverse osmosis concentrate treatment agent.
[0023] Furthermore, the ratio of functional modified bentonite powder, zinc acrylate, N-isopropylacrylamide and ammonium persulfate is 100-110g: 40-50g: 1-2L: 120-130mL: 7-8g.
[0024] The beneficial effects of this invention are:
[0025] 1. The reverse osmosis concentrate treatment agent prepared by this invention involves bentonite powder undergoing alkali washing and acid washing. The surface carboxyl groups and borate groups of phenylboronic acid undergo esterification with the hydroxyl groups of 2,5-hydroxyterephthalic acid. Then, it reacts with titanium tetrachloride in situ via a hydrothermal reaction to generate a titanium-based MOF. After treatment with γ-methacryloyloxypropyltrimethoxysilane, it copolymerizes with zinc acrylate and N-isopropylacrylamide to form a hydrogel membrane. The introduction of boron and zinc elements into the treatment agent, combined with the high specific surface area of the hydrogel membrane and the porosity of the titanium-based structure, significantly increases the adsorption and ion exchange capacity of the treatment agent, thereby significantly enhancing the scale inhibition effect of boron and zinc. When applied in industrial reverse osmosis concentrate treatment, it can effectively remove heavy metals and organic pollutants, reduce the hardness, turbidity, and conductivity of the concentrate, and effectively prevent scaling.
[0026] 2. The reverse osmosis concentrate treatment agent prepared in this invention introduces boron and zinc elements, which can replace traditional phosphorus elements, reducing potential environmental hazards. Furthermore, the high specific surface area and water absorption of the hydrogel membrane enhance the effect of boron and zinc on calcium carbonate and calcium sulfate. Boron and zinc adsorb the active growth points of calcium carbonate and calcium sulfate, interfering with the orderly arrangement of crystals and forming loose and easily detached deformed structures. Unlike phosphorus-based scale inhibitors that contain organophosphonic acids, which easily cause algal blooms and eutrophication after entering water bodies, the fixation of boron and zinc ions through hydrogel and titanium-based MOF increases the long-term effectiveness of boron and zinc ions, avoiding the ineffectiveness of boron and zinc ions due to water flow erosion caused by traditional direct addition, which requires frequent replenishment.
[0027] 3. The reverse osmosis concentrate treatment agent prepared by this invention generates titanium-based MOF in situ on the surface of activated bentonite. During the self-synthesis of titanium-based MOF, boron from phenylboronic acid partially enters the lattice of titanium-based MOF and replaces titanium ions, resulting in a narrower band gap. The narrow band gap broadens the visible light absorption range, improves the utilization rate of sunlight, and is beneficial to the enhancement of the photocatalytic activity of titanium-based MOF.
[0028] 4. The reverse osmosis concentrate treatment agent prepared by this invention utilizes the large specific surface area and ion exchange capacity of bentonite, hydrogel and titanium-based MOF to adsorb various ions in the reverse osmosis concentrate, thereby reducing the conductivity of the reverse osmosis concentrate and effectively preventing scaling. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1: A method for preparing a reverse osmosis concentrate treatment agent, comprising the following steps:
[0031] S1: Add 200g of bentonite powder and 120mL of 6M NaOH solution to a reaction vessel, stir for 6h at 100℃ and 50r / min, filter, wash the filter cake with deionized water and anhydrous ethanol until the last washing liquid is neutral, and dry under vacuum at 100℃ for 10h to obtain alkaline etched bentonite; Add 150g of alkaline etched bentonite and 60mL of 5M HCl solution to a reaction vessel, stir for 6h at 80℃ and 50r / min, filter, wash the filter cake with deionized water and anhydrous ethanol until the last washing liquid is neutral, and dry under vacuum at 100℃ for 10h to obtain activated bentonite powder.
[0032] After being washed with alkali and acid, bentonite powder forms porous corrosion sites on its surface and generates a large number of oxygen-containing functional groups, which facilitates subsequent grafting modification.
[0033] 130g of activated bentonite powder, 50g of phenylboronic acid, 100g of 2,5-hydroxyterephthalic acid, and 2L of deionized water were added to a reaction vessel and stirred at 20℃ and 500r / min for 1h. Then, 6mL of triethylamine was added and stirring was continued for 1h. Next, a mixture of 12g of sodium hexadecyl sulfate and 120mL of 60wt% ethanol solution was added, and the mixture was heated to 120℃ and stirred for 20min. Then, 50g of titanium tetrachloride was added and stirring was continued for 24h. The mixture was filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60℃ for 1h to obtain composite bentonite powder.
[0034] The carboxyl groups in activated bentonite powder and the borate groups in phenylboronic acid undergo an esterification reaction with the hydroxyl groups in 2,5-hydroxyterephthalic acid, and then coordinate with titanium metal to obtain composite bentonite powder.
[0035] Titanium-based MOFs are formed through self-assembly under hydrothermal conditions. During the self-assembly process, boron in phenylboronic acid partially replaces titanium ions, resulting in a narrower band gap. The narrow band gap broadens the visible light absorption range, improves the utilization rate of sunlight, and is beneficial to enhancing the photocatalytic activity of titanium-based MOFs.
[0036] S3: Add 120g of composite bentonite powder, 200mL of anhydrous ethanol and 300mL of deionized water to a reaction vessel, stir for 20min at 50℃ and 500r / min, then add 50mL of γ-methacryloyloxypropyltrimethoxysilane, adjust the pH to 3 with hydrochloric acid solution, continue stirring for 6h, filter, wash the precipitate twice with deionized water and anhydrous ethanol, and vacuum dry at 60℃ for 1h to obtain functional modified bentonite powder.
[0037] γ-Methacryloxypropyltrimethoxysilane is hydrolyzed in ethanol solution to produce silanol groups, which combine with the remaining hydroxyl groups on the surface of composite bentonite powder to obtain functionally modified bentonite powder containing double bonds.
[0038] S4: Add 100g of functional modified bentonite powder, 40g of zinc acrylate, 1L of deionized water and 120mL of N-isopropylacrylamide to a reaction vessel, stir for 20min at 20℃ and 400r / min, heat to 70℃, add 7g of ammonium persulfate, and continue stirring for 6h under a nitrogen atmosphere. Filter, wash the filter cake twice with petroleum ether and deionized water respectively, dry under vacuum at 60℃ for 1h, and pulverize to obtain a reverse osmosis concentrate treatment agent.
[0039] The double bonds in functionally modified bentonite powder, zinc acrylate, and N-isopropylacrylamide are copolymerized under the initiation of ammonium persulfate to obtain a zinc-containing hydrogel film on the surface of the functionally modified bentonite powder. After pulverization, a reverse osmosis concentrate treatment agent is obtained.
[0040] Example 2: A method for preparing a reverse osmosis concentrate treatment agent, comprising the following steps:
[0041] S1: 210g of bentonite powder and 125mL of 6M NaOH solution were added to a reaction vessel and stirred at 105℃ and 55r / min for 6.5h. After filtration, the filter cake was washed with deionized water and anhydrous ethanol until the final washing solution was neutral. The filter cake was then vacuum dried at 105℃ for 11h to obtain alkaline-etched bentonite. 155g of alkaline-etched bentonite and 65mL of 5M HCl solution were added to a reaction vessel and stirred at 85℃ and 55r / min for 6.5h. After filtration, the filter cake was washed with deionized water and anhydrous ethanol until the final washing solution was neutral. The filter cake was then vacuum dried at 105℃ for 11h to obtain activated bentonite powder.
[0042] 135g of activated bentonite powder, 55g of phenylboronic acid, 105g of 2,5-hydroxyterephthalic acid, and 2.5L of deionized water were added to a reaction vessel and stirred at 22.5℃ and 550r / min for 1h. Then, 7.5mL of triethylamine was added, and stirring was continued for 1h. Next, a mixture of 12.5g of sodium hexadecyl sulfate and 130mL of 65wt% ethanol solution was added, and the mixture was heated to 125℃ and stirred for 25min. Then, 55g of titanium tetrachloride was added, and stirring was continued for 25h. The mixture was filtered, and the filter cake was washed 2.5 times with deionized water and anhydrous ethanol, respectively. The mixture was then vacuum dried at 70℃ for 1.5h to obtain composite bentonite powder.
[0043] S3: Add 125g of composite bentonite powder, 250mL of anhydrous ethanol and 350mL of deionized water to a reaction vessel, stir for 25min at 55℃ and 550r / min, then add 55mL of γ-methacryloyloxypropyltrimethoxysilane, adjust the pH to 3.5 with hydrochloric acid solution, continue stirring for 6.5h, filter, wash the precipitate 2.5 times with deionized water and anhydrous ethanol, and vacuum dry at 70℃ for 1.5h to obtain functional modified bentonite powder.
[0044] S4: Add 105g of functionally modified bentonite powder, 45g of zinc acrylate, 1.2L of deionized water and 125mL of N-isopropylacrylamide to a reaction vessel, stir for 25min at 22.5℃ and 450r / min, heat to 75℃, add 7.5g of ammonium persulfate, and continue stirring and reacting for 6.5h under a nitrogen atmosphere. Filter, wash the filter cake 2.5 times with petroleum ether and deionized water respectively, dry under vacuum at 70℃ for 1.5h, and pulverize to obtain a reverse osmosis concentrate treatment agent.
[0045] Example 3: A method for preparing a reverse osmosis concentrate treatment agent, comprising the following steps:
[0046] S1: Add 220g of bentonite powder and 130mL of 6M NaOH solution to a reaction vessel, stir for 7h at 110℃ and 60r / min, filter, wash the filter cake with deionized water and anhydrous ethanol until the last washing liquid is neutral, and vacuum dry at 110℃ for 12h to obtain alkaline etched bentonite; Add 160g of alkaline etched bentonite and 70mL of 5M HCl solution to a reaction vessel, stir for 7h at 90℃ and 60r / min, filter, wash the filter cake with deionized water and anhydrous ethanol until the last washing liquid is neutral, and vacuum dry at 110℃ for 12h to obtain activated bentonite powder.
[0047] 140g of activated bentonite powder, 60g of phenylboronic acid, 110g of 2,5-hydroxyterephthalic acid, and 3L of deionized water were added to a reaction vessel and stirred at 25℃ and 600r / min for 1h. Then, 9mL of triethylamine was added and stirring was continued for 1h. Next, a mixture of 13g of sodium hexadecyl sulfate and 140mL of 70wt% ethanol solution was added, and the mixture was heated to 130℃ and stirred for 30min. Then, 60g of titanium tetrachloride was added and stirring was continued for 26h. The mixture was filtered, and the filter cake was washed three times with deionized water and three times with anhydrous ethanol. The cake was then vacuum dried at 80℃ for 2h to obtain composite bentonite powder.
[0048] S3: Add 130g of composite bentonite powder, 300mL of anhydrous ethanol and 400mL of deionized water to a reaction vessel, stir for 30min at 60℃ and 600r / min, then add 60mL of γ-methacryloyloxypropyltrimethoxysilane, adjust the pH to 4 with hydrochloric acid solution, continue stirring for 7h, filter, wash the precipitate three times with deionized water and anhydrous ethanol, and vacuum dry at 80℃ for 2h to obtain functional modified bentonite powder.
[0049] S4: Add 110g of functional modified bentonite powder, 50g of zinc acrylate, 2L of deionized water and 130mL of N-isopropylacrylamide to a reaction vessel, stir for 30min at 25℃ and 500r / min, heat to 80℃, add 8g of ammonium persulfate, and continue stirring and reacting for 7h under a nitrogen atmosphere. Filter, wash the filter cake three times with petroleum ether and deionized water respectively, dry under vacuum at 80℃ for 2h, and pulverize to obtain a reverse osmosis concentrate treatment agent.
[0050] Comparative Example 1: Based on Example 3, the activated bentonite powder in step S2 was replaced with the bentonite powder in step S1, while the other steps remained unchanged. The mixture was then pulverized to obtain a reverse osmosis concentrate treatment agent.
[0051] Comparative Example 2: Based on Example 3, the functional modified bentonite powder in step S3 was replaced with the composite bentonite powder in step S2, while the other steps remained unchanged. The mixture was then pulverized to obtain a reverse osmosis concentrate treatment agent.
[0052] Comparative Example 3: Based on Example 3, phenylboronic acid in step S2 was omitted, while the remaining steps remained unchanged. The mixture was then pulverized to obtain a reverse osmosis concentrate treatment agent.
[0053] The performance of the reverse osmosis concentrate treatment agents obtained in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are shown in Table 1:
[0054] 1. The reverse osmosis concentrate treatment agent prepared according to this invention was added to 500 mL of a 20 mg / L lead solution with a conductivity of 3830 μs / cm and a 20 mg / L phenol solution. The pH of the solution was adjusted to 6, and the solution was placed on a constant temperature shaker at 25°C and shaken for 24 h at a shaking rate of 200 r / min. The concentrations of calcium ions and manganese ions were determined by atomic absorption spectrophotometry, and the concentration of phenol was determined by 4-aminoantipyrine spectrophotometry. The concentrations of calcium ions, manganese ions, and phenol after treatment were measured to calculate the removal rate of calcium ions, manganese ions, and phenol by the reverse osmosis concentrate treatment agent. The conductivity of the water was measured using a conductivity meter to determine the effect of the reverse osmosis concentrate treatment agent on conductivity.
[0055] 2. Reverse osmosis concentrate was obtained by concentrating wastewater from a chemical fiber industry through reverse osmosis. The concentrate had a sulfate concentration of 16000 mg / L and a calcium hardness of 4500 mg / L. 160 mg / L of the reverse osmosis concentrate treatment agent prepared in this invention and 1.5 mg / L of coagulant polyacrylamide were added to the reverse osmosis concentrate. The hardness and turbidity of the effluent from the reverse osmosis concentrate were then tested.
[0056] Table 1 Performance Test Table of Reverse Osmosis Concentrate Treatment Agent
[0057] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Calcium ions (%) 93.5 94.2 95.2 83.2 80.7 68.9 Manganese ions (%) 94.2 95.1 96.3 84.5 81.6 69.2 phenol(%) 65.5 66.8 67.9 56.5 53.2 42.1 Electrical conductivity (%) 96.5 97.1 97.9 86.2 83.9 72.6 Water hardness (mg / L) 1600 1526 1433 1836 1935 2135 Turbidity (NTU) 10 8 6 15 20 50
[0058] As can be seen from Table 1, the reverse osmosis concentrate treatment agents obtained in Examples 1-3 can effectively remove heavy metals and organic pollutants, reduce the hardness, turbidity and conductivity of the concentrate, and effectively prevent scaling when applied in industrial reverse osmosis concentrate treatment.
[0059] In Comparative Example 1, the activated bentonite powder was replaced with bentonite powder. After alkaline washing and acid washing, the bentonite powder formed porous corrosion sites on its surface and generated a large number of oxygen-containing functional groups, which facilitated subsequent grafting modification. The large porosity also helped to improve ion exchange capacity, which was conducive to loading more titanium-based MOFs and adsorbing various ions in the reverse osmosis concentrate, thereby reducing the conductivity of the reverse osmosis concentrate and effectively avoiding scaling. Therefore, after losing alkaline washing and acid washing, the various properties decreased slightly.
[0060] In Comparative Example 2, the functionally modified bentonite powder was treated with γ-methacryloxypropyltrimethoxysilane to give it double bonds on its surface, which enabled it to copolymerize with zinc acrylate and N-isopropylacrylamide to achieve uniform coverage of the hydrogel film on the bentonite surface. However, without the treatment with γ-methacryloxypropyltrimethoxysilane, the hydrogel film covered the bentonite surface by physical adsorption.
[0061] In Comparative Example 3, phenylboronic acid in step S2 was omitted, while the other steps remained unchanged. Titanium-based MOFs were generated in situ on the surface of activated bentonite. During the self-synthesis of titanium-based MOFs, boron from phenylboronic acid partially entered the lattice of titanium-based MOFs and replaced titanium ions, resulting in a narrower band gap. The narrow band gap broadened the visible light absorption range, improved the utilization rate of sunlight, and was beneficial to the enhancement of the photocatalytic activity of titanium-based MOFs.
[0062] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a reverse osmosis concentrate treatment agent, characterized in that, The steps include: Step 1: After washing the bentonite powder with alkali and acid, activated bentonite powder is obtained. The carboxyl groups and borate groups of phenylboronic acid on the surface of the activated bentonite powder undergo an esterification reaction with the hydroxyl groups of 2,5-hydroxyterephthalic acid. Then, titanium-based MOF is generated in situ with titanium tetrachloride through a hydrothermal reaction to obtain composite bentonite powder. Step 2: Graft the hydroxyl groups on the surface of the composite bentonite powder with the silanol groups generated by the hydrolysis of γ-methacryloyloxypropyltrimethoxysilane to obtain functionally modified bentonite powder. Step 3: A reverse osmosis concentrate treatment agent is obtained by copolymerizing the double bonds in functionally modified bentonite powder, zinc acrylate, and N-isopropylacrylamide under the action of an initiator.
2. The method for preparing a reverse osmosis concentrate treatment agent according to claim 1, characterized in that, The specific preparation steps for the activated bentonite powder are as follows: Bentonite powder and a 6M NaOH solution were added to a reaction vessel and stirred for 6-7 hours at 100-110℃ and 50-60 r / min. The mixture was filtered, and the filter cake was washed with deionized water and anhydrous ethanol until the final washing solution was neutral. The mixture was then vacuum dried at 100-110℃ for 10-12 hours to obtain alkaline-etched bentonite. Alkaline-etched bentonite and a 5M HCl solution were added to a reaction vessel and stirred for 6-7 hours at 80-90℃ and 50-60 r / min. The mixture was filtered, and the filter cake was washed with deionized water and anhydrous ethanol until the final washing solution was neutral. The mixture was then vacuum dried at 100-110℃ for 10-12 hours to obtain activated bentonite powder.
3. The method for preparing a reverse osmosis concentrate treatment agent according to claim 2, characterized in that, The ratio of bentonite powder to NaOH solution is 200-220g: 120-130mL; the ratio of alkali-etched bentonite to HCl solution is 150-160g: 60-70mL.
4. The method for preparing a reverse osmosis concentrate treatment agent according to claim 1, characterized in that, The specific preparation steps of the composite bentonite powder are as follows: Activated bentonite powder, phenylboronic acid, 2,5-hydroxyterephthalic acid, and deionized water were added to a reaction vessel and stirred for 1 hour at 20-25°C and 500-600 r / min. Then, triethylamine was added and stirring was continued for 1 hour. Next, a mixed solution of sodium hexadecyl sulfate and 60-70 wt% ethanol solution was added, and the mixture was heated to 120-130°C and stirred for 20-30 minutes. Then, titanium tetrachloride was added and stirring was continued for 24-26 hours. The mixture was filtered, and the filter cake was washed 2-3 times with deionized water and anhydrous ethanol, respectively. The cake was then vacuum dried at 60-80°C for 1-2 hours to obtain composite bentonite powder.
5. The method for preparing a reverse osmosis concentrate treatment agent according to claim 4, characterized in that, The ratio of activated bentonite powder, phenylboronic acid, 2,5-hydroxyterephthalic acid, deionized water, triethylamine, sodium hexadecyl sulfate, ethanol solution, and titanium tetrachloride is 130-140g: 50-60g: 100-110g: 2-3L: 6-9mL: 12-13g: 120-140mL: 50-60g.
6. The method for preparing a reverse osmosis concentrate treatment agent according to claim 1, characterized in that, The specific preparation steps of the functionally modified bentonite powder are as follows: Composite bentonite powder, anhydrous ethanol, and deionized water were added to a reaction vessel and stirred at 50-60℃ and 500-600 r / min for 20-30 min. Then, γ-methacryloyloxypropyltrimethoxysilane was added, and the pH value was adjusted to 3-4 with hydrochloric acid solution. The reaction was continued to be stirred for 6-7 h. After filtration, washing, and vacuum drying, functional modified bentonite powder was obtained.
7. The method for preparing a reverse osmosis concentrate treatment agent according to claim 6, characterized in that, The ratio of the composite bentonite powder, anhydrous ethanol, deionized water and γ-methacryloxypropyltrimethoxysilane is 120-130g: 200-300mL: 300-400mL: 50-60mL.
8. The method for preparing a reverse osmosis concentrate treatment agent according to claim 1, characterized in that, The specific preparation steps of the reverse osmosis concentrate treatment agent are as follows: Functionally modified bentonite powder, zinc acrylate, deionized water, and N-isopropylacrylamide were added to a reaction vessel and stirred at 20-25℃ and 400-500 r / min for 20-30 min. The mixture was then heated to 70-80℃, and ammonium persulfate was added. Under a nitrogen atmosphere, the mixture was stirred and reacted for 6-7 h. The mixture was then filtered, washed, vacuum dried, and pulverized to obtain a reverse osmosis concentrate treatment agent.
9. The method for preparing a reverse osmosis concentrate treatment agent according to claim 8, characterized in that, The ratio of the functional modified bentonite powder, zinc acrylate, N-isopropylacrylamide, and ammonium persulfate is 100-110g: 40-50g: 1-2L: 120-130mL: 7-8g.
10. A reverse osmosis concentrate treatment agent, characterized in that, The preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
A zero-discharge process and treatment system for cold-rolled reverse osmosis concentrate.
CN113929250B
